Cardiac amyloidosis: where are we today?. (16th June 2015) - Patel, K. S.; Hawkins, P. N.
Abstract Systemic amyloidosis is generally considered to be rare, but the heart is frequently involved and is a major determinant of prognosis. New diagnostic imaging methods have recently been developed with the capacity to enhance the accuracy of diagnosis, which will be ever more important with the variety of new treatments on the near horizon. Most cases of cardiac amyloidosis are of either monoclonal immunoglobulin light chain (AL) type, which can occur at any age from young adulthood onwards, or transthyretin (ATTR) type, which can be acquired in elderly individuals or inherited at a younger age. Cardiac involvement is the most serious manifestation of AL amyloidosis, and serum cardiac biomarkers have proved to be of great value in staging disease severity and response to an ever increasing array of chemotherapy agents. Cardiac involvement is the dominant manifestation of nonhereditary ATTR amyloidosis, also known as senile cardiac amyloidosis, the prevalence of which is not known but is probably much greater than currently recognized. A genetic variant in the gene for transthyretin (TTR), which is present in 3–4% of African Americans and probably a similar proportion of black individuals of African descent generally, appears to be associated with increased susceptibility to developing cardiac ATTR amyloidosis in older age. Several novel therapies are in the advanced stages of development for ATTR amyloidosis including TTR protein stabilizers and RNA inhibitors that greatly diminish TTR production. Here, we will review recent developments in the diagnosis and management of cardiac amyloidosis.